ANALISIS STRATEGI BISNIS MODEL CANVAS DAN CORPORATE LIFECYCLES (STUDI KASUS: UMKM "RAHABAKTI", KABUPATEN LAMONGAN) - Refachlis, Moh Ilham (Jurnal Riset Entrepreneurship, 2022)
UMKM has an important role in economic growth, but amid the COVID-19 pandemic, business actors have experienced a decline or even gone out of business. Business strategy is a major factor in the success or failure of a business, the purpose of this study is to assess the success of UMKM “Rahabakti” in developing its business. This research uses a qualitative descriptive method with data collection through in-depth interviews with business owners, using Miles and Hubermen data analysis techniques and using triangulation techniques as a measure of the validity of the data. The UMKM “Rahabakti” strategy can adjust the product classification according to the intended customer, to be able to maintain business during the pandemic. Based on the business model canvas concept, they can find customer segments according to product value, use media and exhibitions as a channel to sell products, and maintain customer relationships with direct sales, and minimum purchase bonuses as a form of increasing sales and partner stores. Theoretically, the life cycle of the UMKM “Rahabakti” company enters the go-go cycle where they have realized the ideas that have been calculated, so to enter the next stage, UMKM “Rahabakti” needs to enter stages so that they can continue to develop and be sustainable.